Radio-frequency (RF) sensing for deep awareness of human physical status - part VIII. Occupancy detection using IR-UWB - Subramanian Venkat (Nanyang Technological University, 2023)
Academic libraries have undergone renovations to improve the comfort and user experience of their users. During peak times like midterms and finals, libraries tend to be crowded with students seeking a quiet and productive place to work. Students tend to wander around the library to find a study spot which can be time-consuming. In this project, we present a real-time seat occupancy detection system using Impulse Radio Ultra-Wideband (IR-UWB). We used IR-UWB as the radar technology and applied Constant False Alarm Rate (CFAR) and Hidden Markov Model (HMM) for target detection and prediction of seat occupancy state. The system includes a graphical user interface (GUI) application that allows users to select the orientation of the seats and input their coordinates for analysis. The system is able to process the radar signal, perform clutter suppression, and predict the occupancy state of each seat close to real-time. This system can be utilized in various settings such as classrooms, lecture halls, and public transportation to provide real-time seat occupancy information to users.